Design principles of bioinspired interfaces for biomedical applications in therapeutics and imaging - Shih, Chun-Pei; Tang, Xiaofang; Kuo, Chiung Wen; Chueh, Di-Yen; Chen, Peilin (Frontiers in Chemistry, 2022)
In the past two decades, we have witnessed rapid developments in nanotechnology, especially in biomedical applications such as drug delivery, biosensing, and bioimaging. The most commonly used nanomaterials in biomedical applications are nanoparticles, which serve as carriers for various therapeutic and contrast reagents. Since the nanomaterials are in direct contact with biological samples, biocompatibility is one of the most important issues for the fabrication and synthesis of nanomaterials for biomedical applications. To achieve specific recognition of biomolecules for both targeted delivery and biomolecular sensing, it is common practice to engineer the surfaces of nanomaterials with recognition moieties. This mini-review summarizes different approaches for engineering the interfaces of nanomaterials to improve their biocompatibility and specific recognition properties. We also focus on design strategies that mimic biological systems such as cell membranes of red blood cells, leukocytes, platelets, cancer cells, and bacteria.